Seasonality in Antarctic Airborne Fungal Spores - Marshall, W. A. (1997)
Airborne fungal spores were monitored over periods of up to 131/2 months at three sites on Signy Island in the maritime Antarctic. Fungal spore concentrations in the air were much lower than in other parts of the world. Concentrations were very low during the austral winter but increased during the austral summer. Chlamydospores were the most abundant fungal spore type found. Spores of Cladosporium spp. were the second most frequently trapped form. All spore types samples were most abundant in the summer months, except for chlamydospores, which were most numerous during the winter. The concentration of Cladosporium spores in the air at Signy Island was compared with the concentrations of this spore type found in the air in other parts of the world. It was evident that Cladosporium loses its dominance as the most abundant component of the air spora with increasingly high latitude. The peak concentration of fungal spores occurred at two sites following the start of the thaw; at the third site, the peak occurred with the arrival of spores by long-distance transport from more northerly regions.